¿Topología del fantasma? (2008)
ABSTRACT: Topology of the ghost is a challenge, a bet to put the role of the ghost in the clinic and its setting-up on the explanatory horizon getting close to topology. To this, we will divide the work into three parts: First, building the ghost; second, the ghost and its elements: a topology; and third, the ghost in the clinic.